Puzzling market returns of SPACs, Which Frogs Are Turning Into Princes? - Palo, Aleksanteri (My University, 2021)
IPOs by Special purpose acquisition companies’ (SPACs’) have covered over 50% of the total proceeds in U.S. capital markets in the past years. Previous literature has shown that merging with SPACs is an efficient way to become publicly listed, and there are proven advantages, especially for smaller growth companies. SPACs have opened a unique source to raise capital and become publicly traded faster and with fewer hurdles. However, studies have consistently highlighted that SPACs have underperformed the market between 2006 and 2020. Authors have directed criticism towards managing sponsors and stated that the strong incentive of founders drive SPACs to merge with value-destroying terms. Due to the equity compensation, SPACs have been a lucrative investment for sponsors, while common shareholders have paid the price. The primary purpose of this thesis is to examine how an investor can use market information to earn abnormal returns by investing in SPACs? The thesis examines what information is relevant, and what kind SPACs are performing well in the market. In addition, the thesis delivers a comprehensive snapshot of previous literature and the current development of the asset class. The main results show that higher commitment and risk-taking from sponsors lead to better performance. Further, the results support that SPACs, with thresholds that prevent higher dilution rates in the merger, succeed. The results also indicate that the structure of SPACs is evolving and returns are increasing. The market has responded to criticism and is moving towards a more sustainable era, leading to better performance for all shareholders.
Keywords: Special purpose acquisition companies, SPAC